Obeticholic acid and 5β-cholanic acid 3 exhibit anti-tumor effects on liver cancer through CXCL16/CXCR6 pathway - Gou, Haoxian; Liu, Shenglu; Liu, Linxin; Luo, Ming; Qin, Shu; He, Kai; Yang, Xiaoli (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is the most common type of liver malignancy with a high incidence and mortality rate. Previous in vitro and in vivo experiments confirmed that liver sinusoidal endothelial cells (LSEC) secret CXCL16, which works as a messenger to increase the hepatic accumulation of CXCR6+NKT cells and exert powerful antitumor effects. However, evidence for this process in human samples is lacking and its clinical significance is still unclear. In this study, by dissecting human HCC single-cell RNA-seq data, we verified this process through cellphoneDB. Furthermore, we noticed that NKT cells in CXCL16 high expression patients exhibited a higher activation state and produced more IFN-γ compared with CXCL16 low expression patients. We next investigated the differences in gene expression patterns and signaling pathways between activated NKT cells and unactivated NKT cells via NKT cell developmental trajectories and functional enrichment analysis. In vivo experiments, we tested the farnesoid X receptor (FXR) agonist obeticholic acid combined with the takeda G protein coupled receptor 5 (TGR5) antagonist 5β-cholanic acid 3 for the orthotopic liver tumor model. Overall, our research provides the basis and potential strategies for HCC immunotherapy based on NKT cells.